2013
DOI: 10.1111/ejh.12140
|View full text |Cite
|
Sign up to set email alerts
|

To freeze or not to freeze peripheral blood stem cells prior to allogeneic transplantation from matched related donors

Abstract: Infusion of previously frozen stem cells may achieve similar overall outcomes compared to fresh infusion, allowing to program donor apheresis and transplantation. However, cryopreservation might influence on the different pattern of aGVHD, issue that deserves further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Recently, however, it has been shown that 2–3 days of culture and stem cell expansion for patients receiving allogeneic stem cell transfusions may increase cell viability and cell activation readiness [60]. In addition, the use of DMSO as a cryoprotectant may account for the higher incidence of transfusion reactions seen with frozen cells and potentially interfere with therapeutic outcomes [60, 61]. Our group favors fresh cells to frozen cells for therapeutic administration and we believe much of our efficacy data in cats with FCGS and in other ongoing clinical trials are related to the infusion of freshly expanded cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, it has been shown that 2–3 days of culture and stem cell expansion for patients receiving allogeneic stem cell transfusions may increase cell viability and cell activation readiness [60]. In addition, the use of DMSO as a cryoprotectant may account for the higher incidence of transfusion reactions seen with frozen cells and potentially interfere with therapeutic outcomes [60, 61]. Our group favors fresh cells to frozen cells for therapeutic administration and we believe much of our efficacy data in cats with FCGS and in other ongoing clinical trials are related to the infusion of freshly expanded cells.…”
Section: Discussionmentioning
confidence: 99%
“…There remains controversy and a paucity of data, in any given species, to support the use of autologous versus allogenic stem cells in terms of efficacy and outcome [60, 61]. There is some evidence that i.v.…”
Section: Discussionmentioning
confidence: 99%
“…There are emerging data that support the idea that allogeneic stem cell products can be safely cryopreserved . However, reports with cryopreserved PBSCs have also shown increased infusion reactions, delayed PLT engraftment, and possible impact on chronic GVHD . There have also been concerns about reduced function of immune effector T cells with cryopreservation…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreserved products may enhance safety by guaranteeing the availability of a quality‐controlled graft before initiating myeloablative therapy. Although there is no known correlation between the infusion of cryopreserved HPCs and a decreased overall survival and cryopreservation is generally considered to be safe, a few studies previously reported that it is associated with infusion reactions, delayed platelet (PLT) engraftment, and possibly chronic GVHD . To assess whether cryopreservation of the CD34+‐selected product compromises transplant outcomes, we performed a retrospective analysis of neutrophil and PLT engraftment for haploidentical products that were freshly infused versus cryopreserved, thawed, and infused.…”
mentioning
confidence: 99%
“…Similarly, freshly thawed MSCs showed significantly reduced viability (as low as 44%) as well as a decreased ability to suppress T-cell proliferation in vitro and respond to IFN␥ compared to actively growing MSCs (François et al, 2012). Furthermore, the debate on the impact of cryopreservation on allogeneic HSC transplant engraftment and risk of GvHD continues (Frey et al, 2006;Parody et al, 2013). Unsurprisingly, thawed MSCs that were cultured for 24 hours regained these immunomodulatory-linked functions (François et al, 2012) and thawed T regulatory cells that are cultured post thaw also regained their suppressive activity in vitro compared with freshly thawed cells (Peters et al, 2008).…”
Section: Can the Cell Therapy Be Preserved And If So How?mentioning
confidence: 99%